Stone, leaf, and door (an archetypal analysis of Thomas Wolfe's Look Homeward, Angel) - Katalbas, Ruth E. (College of Arts and Letters, University of the Philippines Diliman, 1988)
This thesis is an attempt to analyze Thomas Wolfe's Look Homeward, Angel using an archetypal approach. In Wolfe's novel, one perceives the existence of a particular encompassing archetypal motif - the eternal Romantic Quest for the lost land or paradise of pre-existence. This motif provides the framework for the other meanings and themes that seem to dominate Look Homeward, Angel. By indicating the tracing the various recurrent archetypal images and symbols that embody and convey this motif, the analysis hopes to present and point out that the myth of the lost paradise is the basic idea that unifies and sustains the novel.